Interface entre polidez e impolidez em postagens e comentários de natureza política na página do Facebook da Revista Carta Capital - Martins, Adriana Regina Dantas (2023)
Studies on politeness and linguistic impoliteness are relevant to understanding the interaction between social participants. In this aspect, this thesis aims to analyze the interface between politeness and linguistic impoliteness in ten posts and one hundred and forty-one comments representative of the interactions of Internet users with the author of the post and with other participants on the Facebook page of Carta Capital magazine. As a theoretical and methodological contribution, we took as a basis the studies of Goffman (1967), Leech (1983), Brown e Levinson (1987), Culpeper (1996; 2005), Bravo (1999), Watts (2003), Spencer-oatey (2007), Charaudeau (2011; 2019), Briz (2013), Barros (2017), Amossy (2017); Paiva e Olivera (2019); Cavalcante et al (2020) among others. From the pragmatic-discursive analysis, it was observed that, of the linguistic politeness strategies, the most used were: off record - be ironic; of impoliteness, output of positive impoliteness - make the other feel uncomfortable; output of negative impoliteness - explicitly associate the other to a negative aspect; and, among the strategies resigned for this thesis, the disqualification was the most used in detriment of the attenuation and irony strategies. In the discursive branding action, the negative construction of the image of the person of the post was the most recurrent by the magazine's production; and overall, the engagement of the participants was in favor of the magazine's positioning. These results show that impoliteness was more recurrent in the interactions than politeness. Even in polite interactions, the intent is closer to an impolite action. We also observed that, in the most polemic posts, the interactions, placed in a gradation, are considered more impolite; in the less polemic posts, the gradation varied between more polite, less polite and less impolite. With this investigation, we conclude that there is an interface between politeness and impoliteness, both in the use of verbal and non-verbal text, in posts and comments, showing that the categories of (Im)politeness are at the service of a social participant motivated by the social and interactional context and who presents himself engaged in defending his ideological bias, in which his impolite linguistic choices prevail within a gradation that makes it clear that preserving the face of the self and the other is not always the priority.